Competence building in electric mobility: solving the paradox of specific investments in nascent industries. (1st January 2013) - Gersch, Martin; Rüsike, Tilman; Reichle, Florian
Due to their high degree of uncertainty, nascent industries are of increasing interest in strategic management science. Drawing on the concept of specificity, we analyse the building of resources and competences in the emerging industry of electric mobility. In a qualitative multiple case study on two major car manufacturers and their investments, we show how firms handle the paradox of specific investments. Our results indicate that specificity depends upon strategic management. By varying the degree of specificity, firms can balance the resulting commitment in nascent markets and remain flexible. From a co-evolutionary perspective, firms are driving and are driven by these specific investments. Hence, they continuously engage in creating and securing deployment options for existing resources and competences by (de-)specification strategies but also by trying to shape the firm's environment.